Tinjauan Yuridis Penerapan Asas Praduga Tak Bersalah dalam Trial by the press pada Proses Peradilan Pidana - Suprapto; Tubagus Ahmad Suhendar (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2025)
The media in reporting crimes is considered to have conducted a trial by the press. The press appears to take on the role of law enforcement officers by seeking evidence, interviewing witnesses, analyzing cases, and ultimately judging through their views on a criminal event. Trial by the press is certainly contrary to the principle of the presumption of innocence and an open and impartial trial process (fair trial). Trial by the press was found in press coverage of the Mirna Salihin murder case and the case of celebrity Rachel Venya. This study will examine the influence of trial by the press on the criminal law enforcement process in Indonesia and how the press reports criminal cases in order to avoid trial by the press and to know and understand the regulations on reporting in accordance with the principle of the presumption of innocence in laws and regulations. The research method used is normative juridical using concept analysis, analysis of laws and regulations, and case analysis. This study aims to ensure that the press does not conduct a trial by the press in reporting crimes. The results of the study found that trial by the press resulted in trial by the public so that the public formed an opinion on a criminal case. After the ratification of the New Criminal Code, the press that conducted trial by the press can be sentenced to imprisonment or a fine as regulated in Article 281 of the New Criminal Code and based on the press law.